Pengelolaan Keuangan Keluarga Dalam Rangka Peningkatan Literasi Keuangan Pada Kelompok Tani Di Koya Timur - Ratang, Westim; Wonar, Klara; Tamba, Delima (UNIVERSITAS CENDERAWASIH, 2023)
The link between financial literacy and public access to financial institutions proves that financial literacy has a very important role for society to lead to financial prosperity. In addition, financial literacy makes it easier for individuals and businesses to manage their finances. East Koya is one of the very fertile agricultural areas with producing plantations and also chicken and cattle farms. Much of the income from these farmers has not been used properly and there is a lack of understanding of the farmers in managing existing family finances. The method of training in family financial management in order to increase financial literacy used includes various lectures as an introduction to understanding the principles of financial literacy, especially family finance in improving family businesses. To ensure participants can understand the learning outcomes, at the end of this training a simple survey to test the level of knowledge, attitudes and behavior in managing family finances. The conclusion that can be drawn in managing family finances in order to increase financial literacy in farmer groups in East Koya is that this training can provide increased understanding or level of financial literacy to families in planning and managing their finances properly. Keywords: Family Finances, Financial Literacy, Farmer Groups